2017
DOI: 10.1002/ceat.201700196
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Measuring Gas Solubility in Liquids Using a Tube‐in‐Tube Membrane Contactor

Abstract: A novel approach using a semipermeable Teflon AF-2400 tube-in-tube membrane contactor was developed for the measurement of gas solubility in organic solvents. This membrane ensures gas saturation of liquids in continuous flow at a specific pressure and temperature. After liquid decompression, the amount of gas outgassed was measured with a bubble meter and used for solubility calculation. The proposed method was applied to the measurement of oxygen solubility in toluene and benzyl alcohol. Validation experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The maximum conversion of 31.7 ± 6.1% was consistent with a gas-limited system described by Yang and Jensen based on mass transfer modeling [24]. This result confirmed that the sparger serves to facilitate oxygen solubilization into the liquid stream according to Henry's law, which is a similar result to previous reports for industrially relevant gas/liquid reactions [25,26,28,32]. Conversion can be increased by diluting the substrate; however, dilution decreases the reactor productivity [10,26].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The maximum conversion of 31.7 ± 6.1% was consistent with a gas-limited system described by Yang and Jensen based on mass transfer modeling [24]. This result confirmed that the sparger serves to facilitate oxygen solubilization into the liquid stream according to Henry's law, which is a similar result to previous reports for industrially relevant gas/liquid reactions [25,26,28,32]. Conversion can be increased by diluting the substrate; however, dilution decreases the reactor productivity [10,26].…”
Section: Resultssupporting
confidence: 88%
“…Alternatively, Gavriilidis and co-workers built a tube-in-tube membrane reactor for selective oxidation of neat benzyl alcohol to benzaldehyde [22]. The role of the tube-in-tube membrane reactor was to facilitate the gas oxidant diffusion into the reacting liquid to feed to the catalytic packed bed [8,10,[22][23][24][25][26][27][28][29]. They found that the tube-in-tube reactor improved the catalyst contact with both benzyl alcohol and oxygen simultaneously, resulting in increased conversion and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these considerations, the relatively mild reducing agent CO, was chosen in order to better control the first 'fast reduction' stage instead of cooling reactants as favoured by other researchers. A tube-in-tube contactor was employed to saturate an organic carrier with CO. Based on Henry's law, the amount of dissolved gas in the liquid at equilibrium is proportional to its partial pressure in the gas phase [21]. Therefore the concentration of CO could be tuned by pressurising the microfluidic system.…”
Section: Adaptation Of the Synthetic Process From Batch To Flowmentioning
confidence: 99%
“…With the tube‐in‐tube reactor, they also established an inline titration technique to measure the CO 2 and NH 3 concentration in flowing liquids . 30‐33 Wu and co‐workers have developed a novel method with a bubble meter for measuring gas solubility in organic solvents using a tube‐in‐tube membrane contactor 34 . More recently, by using a gas mass flowmeter to record the change of gas flow rate across the membrane with time, we have built a flow platform for studying gas–liquid systems with the tube‐in‐tube reactor, which have realized the rapid measurement of gas solubility, 22 gas diffusion coefficient in liquids 2 and reaction rate constant of fast gas–liquid reactions 24 .…”
Section: Introductionmentioning
confidence: 99%